Incidence of peripheral arterial disease in diabetic foot - Asif, Mohammad; Basheer, Binshina (International Journal of Research in Medical Sciences, 2025)
Background: Diabetic foot infections (DFIs) are a major cause of morbidity and lower-limb amputations in individuals with diabetes mellitus. Peripheral arterial disease (PAD) significantly increases the risk of non-healing ulcers and adverse outcomes, yet often remains underdiagnosed. This study aimed to determine the prevalence of PAD in patients with DFI and to evaluate its association with clinical profile and outcomes. Methods: A hospital-based descriptive observational study was conducted among 100 adults with DFI. Clinical data were collected using a structured proforma. The severity of foot lesions was graded using the Wagner classification. Ankle–brachial pressure index (ABI) was measured for all participants, and arterial Doppler was performed when ABI was abnormal. Microbiological culture results and need for amputation were recorded. Statistical associations were assessed using Chi-square test. Results: PAD was detected in 60% of patients, with moderate disease being most common. PAD prevalence was significantly higher in older individuals, those with longer diabetes duration, and patients with poor glycaemic control (p<0.05). Overall, amputation rate was 34% (34/100), with significantly higher rates in PAD patients (38.3%) vs non-PAD (27.5%) (p<0.05). Gram-negative organisms predominated in wound cultures, with Pseudomonas (24.0%) and Proteus (17.0%) as the most common isolates. Conclusions: PAD is highly prevalent among hospitalized patients with DFI and is strongly associated with ulcer severity and poor clinical outcomes. Routine ABI-based vascular assessment is essential for early detection and timely intervention to improve limb salvage.